Pengaruh Akuntabilitas Kinerja Pegawai Terhadap Kualitas Pelayanan E-KTP Di Dinas Kependudukan Dan Pencatatan Sipil (DISDUKCAPIL)Kabupaten Nias Selatan - Laia, Swaspril Yohana; Muda, Indra (Mahesa Research Center, 2025)
Quality public services are an important factor in good governance. One of the population administration services that has a strategic role is the issuance of e-KTP by the Population and Civil Registration Office (DISDUKCAPIL). However, in South Nias Regency, this service still faces various obstacles such as limited employees, low understanding of regulations, and inefficient administrative procedures. This study aims to analyze the influence of service quality, employee knowledge, and employee performance on community satisfaction in e-KTP services. The research method uses a quantitative approach with an explanatory format, with samples selected by random sampling. The results of regression analysis show that the three variables simultaneously contribute 49.7% to community satisfaction, with employee performance as the most dominant factor. The results of the t and F tests also showed that the three variables had a significant influence, partially and simultaneously. The implications of this study emphasize the need to increase employee capacity through training, performance evaluation, and service system reform so that e-KTP can be issued more efficiently and increase community satisfaction.